Managing Employees with Disabilities in an Effort to Achieve Workplace Inclusion - Yumni, Raihanah; Aprinawati, Aprinawati; Ambarita, Cristin Melani Br; Syahfitri, Rinanda Suci; Putri, Fitria Anisa; Lubis, Karina Safitri; Hulu, Nutiwati (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This study delves into the complexities of managing employees with disabilities in the pursuit of workplace inclusion. By analyzing existing literature and case studies, the research explores the theoretical underpinnings, practical implementation, and challenges associated with creating inclusive work environments for individuals with disabilities. The findings highlight the critical role of organizational policies, training programs, and accessibility measures in fostering a culture of inclusivity. Furthermore, the study examines the impact of workplace inclusion on both employees with disabilities and the organization as a whole. Key themes emerging from the analysis include the significance of recruitment and selection processes, the importance of providing accommodations and support services, and the need to address attitudinal barriers. The paper concludes by discussing the potential benefits of workplace inclusion, such as increased employee morale, improved organizational reputation, and enhanced innovation.